2005
DOI: 10.1111/j.1442-200x.2005.02121.x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between dietary intake and breast milk dioxin levels in Tokyo, Japan

Abstract: History of breast-feeding and the mother's age should be considered and emphasized in this kind of analysis. The cause effect relationship between dietary intake and breast milk dioxin levels were still uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Nakatani et al (2005) reported TEQs of dl-PCBs in breast milk were correlated with increasing age of mothers in Osaka city, Japan . Guan et al (2005) suggested that the mother’s age should be considered and emphasized in dioxin analysis of breast milk, because in nonpolluted areas, the concentration of dioxin in breast milk is influenced mainly by the mother’s age and history of breastfeeding . Tai et al (2011) reported 2,3,7,8-tetraCDD and TEQ-PCCDs/Fs levels in breast milk were correlated with increasing maternal age, length of residency, and parity in the dioxin contamination hot spot Da Nang, Vietnam .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nakatani et al (2005) reported TEQs of dl-PCBs in breast milk were correlated with increasing age of mothers in Osaka city, Japan . Guan et al (2005) suggested that the mother’s age should be considered and emphasized in dioxin analysis of breast milk, because in nonpolluted areas, the concentration of dioxin in breast milk is influenced mainly by the mother’s age and history of breastfeeding . Tai et al (2011) reported 2,3,7,8-tetraCDD and TEQ-PCCDs/Fs levels in breast milk were correlated with increasing maternal age, length of residency, and parity in the dioxin contamination hot spot Da Nang, Vietnam .…”
Section: Discussionmentioning
confidence: 99%
“…Guan et al (2005) suggested that the mother's age should be considered and emphasized in dioxin analysis of breast milk, because in nonpolluted areas, the concentration of dioxin in breast milk is influenced mainly by the mother's age and history of .25 Tai et al (2011) reported 2,3,7,8-tetraCDD and TEQ-PCCDs/Fs levels in breast milk were correlated with increasing maternal age, length of residency, and parity in the dioxin contamination hot spot Da Nang, Vietnam.1 However, although the results of the present study showed significant correlations of the mother's age with TEQ-PCCDs/Fs and TEQ-nonortho PCBs, this was not observed with 2,3,7,8-tetraCDD. Parity and length of residency were highly correlated with 2,3,7,8-tetraCDD.…”
mentioning
confidence: 99%
“…28 Levels of PCBs are generally higher in the breast milk of European and North American women than in women from non-industrialised countries. Guan found higher levels of three dioxins in the milk of lactating mothers eating a lot of fatty meat and fish, 29 precisely the diet of seabirds and fish on St Kilda. Barraza-Vazquez 30 demonstrated a positive correlation between the maternal venous blood and umbilical cord levels of dichlorodiphenyltrichloroethane (DDT).…”
Section: Human Studiesmentioning
confidence: 93%
“…These studies also suggest that human intake of dioxin has been decreasing for several decades [2][3][4][5][6]. Moreover, several studies have reported positive correlations between the intake of fish and dairy products and dioxin concentrations in breast milk, which are the specific factors influencing the accumulation of dioxin in humans [7][8][9]. There have, however, been few studies in Vietnam, in spite of the fact that a great deal of herbicide was sprayed there.…”
Section: Introductionmentioning
confidence: 99%